Faktor-Faktor yang Berhubungan dengan Tingkat Stress Remaja yang Melakukan Home Learning Selama Pandemi Covid-19 - Sianturi, Sondang Ratnauli; Putri, Yohana; Hidayah, Ainum Juhariah (Poltekkes Kemenkes Padang, 2023)
During the Covid-19 pandemic, teenage students carried out online/home learning, and most of them had problems in implementing it. The aim of this research is to identify factors related to stress levels during home learning. A correlational descriptive research design with a cross-sectional approach and a total sampling technique was carried out in April 2021. The population in this study was 322 students in class XI at SMAN 10 Bekasi with a sample of 153 respondents. Univariate results show that the majority of respondents (43.8%) have normal stress levels, 67.3% of respondents have type B personality, 68% of respondents have parental support, 38.6% of respondents experience sometimes poor internet connection, and 74.5% respondents used the blended learning method. Bivariate analysis of this research using the Chi Square and Kendall's Tau-C tests showed that there was a significant relationship between personality type (pvalue 0.002) and family support (pvalue 0.027) with stress levels, and there was no relationship between internet connection (pvalue 0.586) and learning methods (pvalue 0.539) with stress levels. Conclusion: The respondent's stress level is influenced by a person's personality type and the presence of family support. It is recommended that educational institutions know students' personality types so that they can assist them according to their characteristics and strong motivation from the family and school environment.